Digital learning: WhatsApp as a teaching aid in oral pathology for undergraduates - M Indu; Shalu Kandhol; Latha Mary Cherian (Wolters Kluwer Medknow Publications, 2018)
Background: Influence of social media such as WhatsApp is tremendously increased among students. The query aroused was whether such a familiar platform could be used as a learning tool. Objectives: The purpose of the study was to assess the effectiveness of WhatsApp as an educational tool in a complex subject such as oral pathology among undergraduate students. Methods: Third-year students of Government Dental College, Alappuzha, were selected as the study population and were divided into Group A and Group B by a simple random sampling. Histopathology slides were discussed conventionally with both Group A and Group B. Furthermore, labeled histopathological images were discussed only for Group A students, in a WhatsApp group named "GDC ALLEPPEY OPATH." To assess the effectiveness of a new method, a questionnaire was given to both groups and the results were statistically analyzed using Mann-Whitney U-test. An additional opinion poll was carried out with Group A to identify students' perspective toward the novel learning tool. Results: Pair-wise comparison of the mean scores of Group A and Group B showed a statistically significant higher mean score for Group A (P = 0.005). There was a significant improvement in the mean score of Group A in their ability to comprehend individual histopathologic features compared to that of Group B (P = 0.008). Conclusion: WhatsApp can prove to be highly advantageous and enhance learning in undergraduate students when used in supplementation to the conventional learning methods.